2021
DOI: 10.1080/01419870.2021.1943483
|View full text |Cite
|
Sign up to set email alerts
|

Gate-keeping the nation: discursive claims, counter-claims and racialized logics of whiteness

Abstract: This article analyses the racialization of discourses about national identities, and explores the implications for populations racialized as white. Two extensive datasets have been brought together, spanning a decade and 560 interviews, to explore discursive interplay, the oppositional nature and relationality of majority and minority claims about national belonging. We demonstrate that national identity claims are constructed discursively from positions of relative advantage and disadvantage: here the English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Works have also shown that the Polish national football team is popularly understood to serve as an embodiment and representation of the nation and its values (Jaskułowski and Majewski, 2016;Maguire et al, 2009). Elgenius and Garner (2021) argue that previous works have often overlooked how race/ethnicity is a constituent factor in dominant discourses about national belonging. This mutually entangled production of racial/ethnic and national categories and hierarchies can also be witnessed in the Polish public context, where, as Krzyżanowski (2020) argues, a resurgence of ethno-nationalism has gone hand in hand with the increasing legitimacy of racializing discourses.…”
Section: National Football and Race/ethnicitymentioning
confidence: 93%
See 2 more Smart Citations
“…Works have also shown that the Polish national football team is popularly understood to serve as an embodiment and representation of the nation and its values (Jaskułowski and Majewski, 2016;Maguire et al, 2009). Elgenius and Garner (2021) argue that previous works have often overlooked how race/ethnicity is a constituent factor in dominant discourses about national belonging. This mutually entangled production of racial/ethnic and national categories and hierarchies can also be witnessed in the Polish public context, where, as Krzyżanowski (2020) argues, a resurgence of ethno-nationalism has gone hand in hand with the increasing legitimacy of racializing discourses.…”
Section: National Football and Race/ethnicitymentioning
confidence: 93%
“…This region proves particularly interesting since in many of its national contexts a resurgent ethno-nationalism explicitly points to the mutual constitution of racialized hierarchies, and discourses of national belonging and deservingness (Elgenius and Garner, 2021; Krzyżanowski, 2020). Deservingness here refers to the discursive (re)construction of hierarchies and borders of the national imaginary by majority groups (Elgenius and Garner, 2021). However, little attention has been paid to how this mutual constitution might be discursively (re)produced in sport media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another body of work has explored activity in relation to refugees (Phillimore and Goodson, 2010;Benson, 2017). Qualitative studies have problematised claim-making, contestation, identities and practices around key themes, including the ethnic framing of heterogenous populations (Brubaker, 2005) and racialised logics (Elgenius and Garner, 2021). Yet, we raise two concerns that such approaches may unwittingly re-enforce groupism, albeit in a different way to quantitative approaches, and that they tend to be disconnected from quantitative civil society research.…”
Section: Qualitative Studies and Methodological Nationalismmentioning
confidence: 99%
“…The salience of the economic cleavage dimension has decreased, and fewer people use class frames in understanding the world and their being in the world. Thus, clashes of economic interests or a threat against status and position are today increasingly mobilized by frames stressing the distinction between “immigrants” and “natives.” For instance, the discourse of the left‐behind, used during the Brexit campaign in 2016, stressed clashing economic interests by way of distinguishing between the entitled and others within frames of nostalgia and belonging, explaining sentiments of entitlement and resentment (Elgenius and Garner 2021). The discourse of the left‐behind—the limited options of the less educated, the disenfranchised and disadvantaged—made it into the public with references to the “white British working class” or the “white English working class” tricked out of their rights.…”
Section: Framing Struggles and Clashing Nostalgiamentioning
confidence: 99%